A 40-year climatological study of relative vorticity distribution over the Mediterranean - Flocas, H.A.a; Maheras, P.b d; Karacostas, T.S.b; Patrikas, I.c; Anagnostopoulou, C.b (International Journal of Climatology, 2001)
A climatological study of the spatial and temporal distribution of mean relative geostrophic vorticity over the Mediterranean region is examined for a period of 40 years (1958-1997). Two major cyclonic vorticity maxima are found in the Mediterranean at low levels, one covers the Gulf of Genoa and south Italy and the second is located over the southeastern Aegean Sea with different diurnal and seasonal characteristics, controlling cyclone formation. At upper levels, a large scale cyclonic vorticity zone covers the whole Mediterranean region with notably increased values at 300 hPa, being associated with jet stream dynamics, especially in the eastern Mediterranean. The seasonal changes of the horizontal vorticity distribution substantially reduce with height while the diurnal changes become unimportant at upper levels. Furthermore, the investigation of the vertical structure separately for the main cyclonic centres in the Mediterranean implies the different mechanisms that are reponsible for cyclone formation in the western and eastern basin. Copyright © 2001 Royal Meteorological Society.
Keywords: Climate change; Climatology; cyclogenesis; geostrophic flow; Mediterranean Region; Mediterranean Sea; Oceanography; spatiotemporal analysis; Storms; Vertical structures; Vortex flow; vorticity